A Review of Carbohydrate Nutrition and Metabolism in Crustaceans. (4th April 2016) - Wang, Xiaodan; Li, Erchao; Chen, Liqiao
Abstract: Carbohydrates are the primary energy source in all animal diets and are the least expensive energy source in the diets of aquatic animals. However, the utilization of carbohydrates by aquatic animals is relatively low relative that of terrestrial animals. Compared with those in fish, few studies have examined the nutrition or metabolism of crustacean species. This lack of information is a bottleneck for current research of crustacean physiology, especially that which focuses on nutrition. Specifically, there is a deficiency of research that focuses on glucose transporter proteins (except for glucose transporter (GLUT) family protein), regulators involved in carbohydrate metabolism, and the interaction of different hormones. This paper summarizes the dietary carbohydrate requirements of various crustacean species and reviews the progress of research on carbohydrate utilization and metabolism, with an aim to providing clearer insight into carbohydrate metabolism and laying a theoretical foundation for crustacean physiological research.